Analysis of Mathematical Connection Ability with Contextual Learning Model of Simple Fraction Material for Class III in School: Analisis Kemampuan Koneksi Matematika dengan Model Pembelajaran Kontekstual Materi Pecahan Sederhana Kelas III di Sekolah - Ulfiyyatur Rosyidah; Nur Efendi (Academia Open, 2022)
Knowing the application of the contextual learning model can be applied in the modeling connections and mathematical connections approach in mathematics lessons on simple fraction material for third grade students of SDN Sepande and knowing the responses of SDN Sepande students to learning simple fraction mathematics by applying the contextual model. In learning mathematics, each student has different abilities. Problems that are often found by elementary school (SD) students in their daily life are problems related to simple fractions in mathematics lessons. Because the concept of fractions is often found in student activities in carrying out various activities in daily life, Elementary School students are no exception. Based on this, the contextual learning model can improve the mathematical connection ability of students. This research method uses qualitative methods with a narrative approach. The population in this study is SDN Sepande Sidoarjo, the object of this research is the third grade students. Using the following instruments: test questions, student response questionnaires, interviews, and observation sheets. The results of this study indicate the difference in the average pretest and posttest data of the experimental group using triangulation techniques. In the results of this study, there are 3 levels of mathematical connection ability at high, medium, and low levels. In the contextual learning model it can make it easier for students to solve simple fraction problems.